Posttraumatic inflammation as a key to neuroregeneration after traumatic spinal cord injury - Moghaddam-Alvandi, Arash; Child, Christopher; Bruckner, Thomas; Gerner, Hans-Jürgen; Daniel, Volker (International journal of molecular sciences, 2015)
Pro- and anti-inflammatory cytokines might have a large impact on the secondary phase and on the neurological outcome of patients with acute spinal cord injury (SCI). We measured the serum levels of different cytokines (Interferon-γ, Tumor Necrosis Factor-α, Interleukin-1β, IL-6, IL-8, IL-10, and Vascular Endothelial Growth Factor) over a 12-week period in 40 acute traumatic SCI patients: at admission on average one hour after initial trauma; at four, nine, 12, and 24 h; Three, and seven days after admission; and two, four, eight, and twelve weeks after admission. This was done using a Luminex Performance Human High Sensitivity Cytokine Panel. SCI was classified using the American Spinal Injury Association (ASIA) Impairment Scale (AIS) at time of admission and after 12 weeks. TNFα, IL-1β, IL-6, IL-8, and IL-10 concentrations were significantly higher in patients without neurological remission and in patients with an initial AIS A (p < 0.05). This study shows significant differences in cytokine concentrations shown in traumatic SCI patients with different neurological impairments and within a 12-week period. IL-8 and IL-10 are potential peripheral markers for neurological remission and rehabilitation after traumatic SCI. Furthermore our cytokine expression pattern of the acute, subacute, and intermediate phase of SCI establishes a possible basis for future studies to develop standardized monitoring, prognostic, and tracking techniques.